Avaliação da expressão gênica de pericitos de lesão neoplásica intraepitelial prostática de camundongos Hi-Myc - Pedro Henrique Dias Moura Prazeres (2020)
Prostate cancer displays high prevalence and mortality in both the Brazilian population and around the world. Prostate cancer progression initiates, in general, from the expression of oncogenes or suppression of tumor suppressor genes in epithelial cells. The proliferation of these cells marks the onset of prostatic intraepithelial neoplasias (PIN), which are not able to invade the surrounding tissues, but leads to a response of stromal cells that finally alter the prostate microenvironment. PINs can evolve in grade and originate invasive adenocarcinomas. An alternative to studying the tumor microenvironment and the alterations involved in the formation of lesions is the use transgenic mouse models. These models allow the evaluation of different stages of the lesions and how the cellular components of the microenvironment are altered during the process. An important cell population present within the tumor microenvironment is pericytes, which are located around the blood vessels, control vascular permeability and tension and are highly plastic. Pericytes respond to stimuli in different types of lesion, and can be altered by the microenvironment favoring the regeneration of the tissue. Thus, we focused on studying the expression of genes involved in tumor progression in different stages of PIN as a way to explore the role of pericytes in pre-malignant lesions. In this work we used mice that develop PIN by the expression of c-Myc specifically in prostate epithelial cells and express endogenous fluorescence in pericytes. Prostatic lesions in the mice were characterized at 6 and 12 months of age as high and low grade respectively. Pericytes were identified within these lesions, and their number and coverage area increased as the lesion progressed. To study gene expression of pericytes a protocol for isolating these cells based on their fluorescence was stablished. We analyzed a panel of 84 genes commonly involved in prostate cancer in pericytes isolated from different stages of PIN, as well as from healthy prostates. Gene expression data show that some tumor suppressor genes are upregulated in high grade lesions (Gpx3, Gstp1, Rb1, Sfn e Sfrp1), whereas another is downregulated (Ints6). Other genes associated with normal prostatic functions, cell cycle regulation and apoptosis were upregulated in both stages (AR, Cav2, Pten e Trp53). Contrastingly, other tumor suppressor genes were downregulated in both stages of the lesion (Dab2ip e Dkk3), which raises the hypothesis that epigenetic factors might influence the role of these genes in pericytes of pre-malignant prostatic lesions. The correlation of these genes with the survival of patients with prostate cancer was assessed in a public available database. Survival data suggest that high expression of Gpx3 and Timp3 associates with a reduction in patient survival, when compared to patients with low expression, which validates the importance of evaluating gene expression as a tool in the clinical management of neoplasias.